Mechanical Control of Individual Superconducting Vortices - Kremen, Anna (Nano Lett, 2016)
[Image: see text] Manipulating individual vortices in a deterministic way is challenging; ideally, manipulation should be effective, local, and tunable in strength and location. Here, we show that vortices respond to local mechanical stress applied in the vicinity of the vortex. We utilized this interaction to move individual vortices in thin superconducting films via local mechanical contact without magnetic field or current. We used a scanning superconducting quantum interference device to image vortices and to apply local vertical stress with the tip of our sensor. Vortices were attracted to the contact point, relocated, and were stable at their new location. We show that vortices move only after contact and that more effective manipulation is achieved with stronger force and longer contact time. Mechanical manipulation of vortices provides a local view of the interaction between strain and nanomagnetic objects as well as controllable, effective, and reproducible manipulation technique.